The evolution of Global Libraries' performance measurement and impact assessment systems. Issue 2 (13th July 2015) - Streatfield and Jeremy Paley, David; Paley, Jeremy; Cottrill, Julia; Errecart, Katherine; White, Aimee; Schaden, Carrie; Schrag, Tyler; Douglas, Robert; Tahmassebi, Beeta; Crocker, Rachel; Streatfield, David
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to describe the evolution of a common approach to impact assessment across the Global Libraries (GL) portfolio of grants. It presents an overview of two systems, the Performance Metrics (PMs) and the Common Impact Measurement System (CIMS). By providing a standard set of definitions and methods for use across countries, these systems enable grantees to collect data that can be compared and aggregated for the purpose of collective learning, improvement, accountability, and advocacy. Design/methodology/approach – The PMs offer a standard methodology to collect library project performance management data, whereas the CIMS is a standard survey of public library users. The paper describes how the PM and CIMS data are being visualized and used, with examples of findings and lessons learned. Findings – The paper cites examples of the type of PM and CIMS data available, with a focus on employment, gender, and case studies from Botswana and Indonesia. These highlights illustrate how libraries' user demographics differ from other types of public internet access venues and how libraries can contribute to strong employment and growth. Research limitations/implications – The measurement systems rely on different partners collecting data for the same metrics across different countries; while each grantee adheres to a standard methodology, small procedural, and methodological differences are inevitable. Future research could focus on conducting similar studies elsewhere, outside the cohort of countries in the GL portfolio of grants. Practical implications – The paper offers insights and lessons for library agencies or institutions interested in implementing a common measurement system. Recognizing that few library projects have the resources to track a comprehensive set of indicators, a case study is presented about how smaller initiatives can adapt these systems to their needs. Social implications – The indicators described in this paper enable public libraries to shift their focus from services provided to the outcomes they help individuals and communities realize, potentially increasing the potency of their programming and advocacy. Originality/value – Common measurement systems are not new, but their application in the public library field is novel, as is the Data Atlas, a platform grantees use to compare results across metrics, track progress, and conduct advocacy.